Respuesta :

Answer:

x^2 -6x+44

Step-by-step explanation:

Develop form of (x-3)^2 is x^2 - 6x +9

Then y= x^2 -6x +9 + 35

So, y= X^2 -6x +44

Answer:

[tex]y=x^2 -6x+44[/tex]

Step-by-step explanation:

The standard form of a quadratic equation is:

[tex]y = ax ^ 2 + bx + c[/tex].

In this case we have the following quadratic equation in vertex form

[tex]y=(x-3)^2+35[/tex]

Now we must rewrite the equation in the standard form.

[tex]y=(x-3)(x-3)+35[/tex]

Apply the distributive property

[tex]y=x^2 -3x -3x +9+35[/tex]

[tex]y=x^2 -6x+9+35[/tex]

[tex]y=x^2 -6x+44[/tex]

the standard form of the equation is: [tex]y=x^2 -6x+44[/tex]